2020
DOI: 10.12659/msm.921745
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hetiao Jianpi Decoction on Intestinal Injury and Repair in Rats with Antibiotic-Associated Diarrhea

Abstract: Background:Through observing the changes of indexes of the intestinal mucosal barrier and intestinal flora in rats, we explored the mechanism by which Hetiao Jianpi Decoction (HTJPD) treats antibiotic-associated diarrhea (AAD) by repairing intestinal mucosal injury and regulating intestinal flora. Material/Methods:Samples of colon tissues were collected for HE staining. Enzyme-linked immunosorbent assay (ELISA) was used to assess levels of diamine oxidase (DAO) and D-lactic acid in rat plasma and the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Importantly, accumulating studies have indicated that Verrucomicrobia and Akkermansia are closely related to diarrhea and the intestinal mucus barrier. Therefore, we hypothesized that QBD treatment modulates the gut microbiota and repairs the mucus barrier in juvenile diarrheal rats by the following mechanism: (1) QBD treatment prompts an increase in Verrucomicrobia abundance and thereby improves the intestinal barrier [ 57 ]. (2) QBD treatment increases the abundance of Akkermansia , the most representative bacteria in the phylum Verrucomicrobia.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, accumulating studies have indicated that Verrucomicrobia and Akkermansia are closely related to diarrhea and the intestinal mucus barrier. Therefore, we hypothesized that QBD treatment modulates the gut microbiota and repairs the mucus barrier in juvenile diarrheal rats by the following mechanism: (1) QBD treatment prompts an increase in Verrucomicrobia abundance and thereby improves the intestinal barrier [ 57 ]. (2) QBD treatment increases the abundance of Akkermansia , the most representative bacteria in the phylum Verrucomicrobia.…”
Section: Discussionmentioning
confidence: 99%
“…Verrucomicrobia and Akkermansia are closely associated with diarrhea and the intestinal mucus barrier. Verrucomicrobia is mainly concentrated in the mucus layer of the intestine and is considered to be an indicator of a healthy intestine due to its immunostimulatory properties and ability to improve the intestinal barrier [ 59 ]. Akkermansia is a mucin-degrading bacterium that resides in the mucus layer and has the ability to stimulate mucin synthesis, restore the thickness of the mucus layer and the number of cupped cells, and thereby improve the barrier function of the intestinal mucus layer [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The equation used for this purpose was rat dose = human daily dose × rat conversion factor/rat weight, the rat conversion factor used was 0.018, considering average masses of 70 kg for human and 0.2 kg for rat (Wang and Feng 2019 ; Li et al. 2020 ). The results of this equation were rounded up to a dose of 2 mg/kg bodyweight.…”
Section: Discussionmentioning
confidence: 99%